The QUEECA Experience Developing and Implementing a Central Asia Accreditation of Engineering Education Consistent with European Standards - Gerasimov, Sergey; Guberti, Elisa; Quadrado, Jose Carlos; Umankulova, Onola; Winkelmann, Ulf; Borri, Claudio (Proceedings e report, 2016)
QUEECA is a Tempus project which aims at setting up and implementing a system of Quality Assurance of Engineering Education (EE) in Central Asia countries, finalized to the pre-professional accredition of engineering programmes (i.e. accredition of educational programmes as entry route to the eng. profession). The accredited programmes must satisfy the same pre-requisites for the award of the EUR-ACE quality label, i.e. the EUR-ACE Framework Standards (EAFS) and the European Standards and Guidelines for Quality Assurance in Higher Education.